Subjective Well-Being Pada Pasangan Yang Menikah Muda - Miswiyawati, Danis; , Rini Lestari, S.Psi, M.Si (2017)
Young individual often compares their life with another standart or to compare their life with previous living. Adjustments to the comparison is what will bring a positive or negative impact and prosperous young age whether or not the individual in carrying out his new role as a partner in a marriage. The purpose of this study is to determine and describe subjective well-being on a young married couple. This study used a qualitative approach. Subjects in this study were 3 pairs of husband and wife who married young. The collections of data used in this study were interviews. Analysis of the data used in this research is content analysis. The results of the study illustrate that young married couple who feel Subjective well-being enough high in marriage. Subjective well-being established with the young couples that young couples can accept the conditions he has experienced and grateful for what happened. Overall youn couples often fell more positive affect than negative affect. Factors that influence the subjective well-being on a young married are optimism, positive relationships, have ideals